Nilai-Nilai “Markobar” Dalam Pernikahan Adat Mandailing Dan Keterkaitannya Dengan Bimbingan Konseling Islami - Harahap, Rizka Indah Fadhila; Ritonga, Hasnun Jauhari (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to find out what are the values contained in the custom of "markobar" seen from the aspects of each clan at the time of the implementation of mandailing traditional marriage and its relation to Islamic counseling guidance. The supporting theories in this study are the markobar customary tradition and Islamic counseling guidance. The method in this study used is a qualitative method with descriptive type and data collection techniques in this study with interviews, observation, documentation and literature study as data collection. Then the results of the study show that, the values in the "markobar" custom from the aspect of each clan have a relationship with the values in Islamic counseling guidance, the "markobar" custom is considered to have a relationship with Islamic counseling guidance because in the "markobar" custom there is advice or guidance value, social value, spiritual value and there is a meaning of advice value and aqidah value, the same social value as Islamic counseling guidance. However, there are differences in that the markobar custom is carried out by traditional leaders, families, while in Islamic counseling guidance is carried out by an expert (professional) to the counselee and can be provided in the long term and short term in Islamic guidance and counseling services.